ANALISA DAMPAK PENERAPAN SISTEM LALU LINTAS SATU ARAH PADA SIMPANG 3 STRAT-A TERHADAP ARUS LALU LINTAS SERTA KINERJA LAHAN PARKIR DI PASAR TRADISIONAL OEBA KOTA KUPANG - Bolla, Margareth E.; Messah, Yunita A.; Laning, Rezky L. (Jurnal Teknik Sipil, 2016)
This study aims to determine the impact of the implementation of one-way traffic system simulated at the three-legged signalized intersection on Straat A towards the traffic flow, and the performance of parking area at Oeba, a traditional market in Kupang City. The analysis involves comparing the volume of vehicles and the performance of the parking area before and during the implementation of one-way traffic system simulation with the parking space requirements as well as the design models of parking spaces. The analysis shows that the implementation of one-way traffic system simulation affects the increase of traffic volume in one access that is at Cabang Air-Oeba, but overall it does not affect the increase of traffic volume in general. The result of the performance analysis on the market's parking area reveals to be in trouble, with the parking index value that is greater than 1 (one). Based on that index value, the addition of a parking area is needed as follows: 357 m2 for motorcycles, 637.50 m2 for light vehicles and 680 m2 for heavy vehicles. In order to overcome this problem the government has prepared a new parking area with the width 1011 m2, but this additional parking area is not yet sufficient, so that the government still needs to provide 663.50 m2 as the new additional parking area.